If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 3tx + -5x Solving 3 = 3tx + -5x Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3tx' to each side of the equation. 3 + -3tx = 3tx + -3tx + -5x Combine like terms: 3tx + -3tx = 0 3 + -3tx = 0 + -5x 3 + -3tx = -5x Add '-3' to each side of the equation. 3 + -3 + -3tx = -3 + -5x Combine like terms: 3 + -3 = 0 0 + -3tx = -3 + -5x -3tx = -3 + -5x Divide each side by '-3x'. t = x-1 + 1.666666667 Simplifying t = x-1 + 1.666666667 Reorder the terms: t = 1.666666667 + x-1
| cos(x)+cos(3x)=2sen(6x)cos(x) | | -4=-2(8x-12) | | 3=3t*-5x | | cos(x)+cos(3x)= | | Y-14=4(x-2) | | b=(3.14)(12)2 | | 5x*5x-15x-50=0 | | s*5-22=98 | | 5w-11=89 | | 9x-2=5x+8 | | 5x-10xy=5(x-2y) | | 5x-4=10y | | 2x+9=5x+54 | | 2x+15=x+16 | | 5/9+2/9= | | -6-2(m+4)=36 | | 3y-11=2y-6 | | 4x-5(2x+1)=7x+3(4x-5) | | 3/2-2/7= | | x+x+x+2=3+2x | | 4.9-5.2=4.7 | | x+x+x+2=3x+2 | | 0=80x-x | | 7x-6=3x+54 | | 4d+6+2d=6(d+6) | | -6x-12+8x-21=-6 | | x*1.012048193=84 | | -3x+11+5x+17=4 | | (4x-5)(2x+1)=0 | | 2(3d+3)=4d+6+2d | | 84y-1*y=84 | | 1.9x+2.4=8.9 |